Perancangan UI/UX Sistem Informasi Surat Pengantar Dengan Metode Design Thinking Desa Legoksari Purwakarta - Adrian, Muhamad Adlan; Siregar, Juarni (Journal of Information System, Applied, Management, Accounting and Research, 2026)
Population administration services in Legoksari Village, Darangdan Subdistrict, Purwakarta Regency, currently face significant efficiency challenges due to the conventional, paper-based process of handling referral letters (surat pengantar). Residents are required to visit the village office in person, which is often time-consuming, hinders productivity, and is prone to human errors in data management. Furthermore, the lack of a centralized digital platform limits the speed of public service delivery. This research aims to design a User Interface (UI) and User Experience (UX) for a digital-based referral letter information system tailored to the specific needs and digital literacy levels of both residents and village officials. The method employed in this study is Design Thinking, which consists of five iterative stages: Empathize, Define, Ideate, Prototype, and Test. This approach was selected for its focus on human-centered design, ensuring that the resulting application is intuitive and accessible for various age groups within the Legoksari Village community. By emphasizing empathy, the design specifically addresses the pain points experienced by the local community during administrative tasks. The output of this research is a high-fidelity prototype of the referral letter information system. Based on comprehensive testing conducted through the System Usability Scale (SUS), this design is expected to significantly improve service time efficiency, minimize data redundancy, and provide seamless access for residents to apply for referral letters independently. Ultimately, the implementation of this design is intended to serve as a strategic foundation for more transparent, modern, and responsive public service digitalization at the village level in Purwakarta. The form of the letter after the digitalization process has changed, namely the signature and stamp which were originally in wet form have become in the form of a QRcode.Population administration services in Legoksari Village, Darangdan Subdistrict, Purwakarta Regency, currently face significant efficiency challenges due to the conventional, paper-based process of handling referral letters (surat pengantar). Residents are required to visit the village office in person, which is often time-consuming, hinders productivity, and is prone to human errors in data management. Furthermore, the lack of a centralized digital platform limits the speed of public service delivery. This research aims to design a User Interface (UI) and User Experience (UX) for a digital-based referral letter information system tailored to the specific needs and digital literacy levels of both residents and village officials. The method employed in this study is Design Thinking, which consists of five iterative stages: Empathize, Define, Ideate, Prototype, and Test. This approach was selected for its focus on human-centered design, ensuring that the resulting application is intuitive and accessible for various age groups within the Legoksari Village community. By emphasizing empathy, the design specifically addresses the pain points experienced by the local community during administrative tasks. The output of this research is a high-fidelity prototype of the referral letter information system. Based on comprehensive testing conducted through the System Usability Scale (SUS), this design is expected to significantly improve service time efficiency, minimize data redundancy, and provide seamless access for residents to apply for referral letters independently. Ultimately, the implementation of this design is intended to serve as a strategic foundation for more transparent, modern, and responsive public service digitalization at the village level in Purwakarta. The form of the letter after the digitalization process has changed, namely the signature and stamp which were originally in wet form have become in the form of a QRcode.